(x2 + 4x + 8)(2x - 1)

Question

Asked 11/17/2014 12:59:26 PM

Updated 11/17/2014 1:19:42 PM

2 Answers/Comments

Flagged by alfred123 [11/17/2014 1:15:01 PM]

s

Question

Asked 11/17/2014 12:59:26 PM

Updated 11/17/2014 1:19:42 PM

2 Answers/Comments

Flagged by alfred123 [11/17/2014 1:15:01 PM]

Rating

8

(x^2 + 4x + 8)(2x - 1)

= 2x^3 - x^2 + 8x^2 - 4x + 16x - 8;

=2x^3 + 7x^2 + 12x - 8

= 2x^3 - x^2 + 8x^2 - 4x + 16x - 8;

=2x^3 + 7x^2 + 12x - 8

Added 11/17/2014 1:16:37 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/17/2014 1:25:09 PM]

8

(y + z)^3

= (y + z)(y + z)(y + z)

= (y^2 + yz + yz + z^2)(y + z);

= (y^2 + 2yz + z^2)(y + z);

= y^3 + y^2z + 2y^2z + 2yz^2 + yz^2 + z^3;

= y^3 + 3y^2z + 3yz^2 + z^3

= (y + z)(y + z)(y + z)

= (y^2 + yz + yz + z^2)(y + z);

= (y^2 + 2yz + z^2)(y + z);

= y^3 + y^2z + 2y^2z + 2yz^2 + yz^2 + z^3;

= y^3 + 3y^2z + 3yz^2 + z^3

Added 11/17/2014 1:19:42 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/17/2014 1:26:24 PM]

What is the product of (n - 8)(n + 2)?

Question

Updated 12/4/2014 10:13:56 PM

2 Answers/Comments

(n - 8)(n + 2) = n^2 + 2n - 8n - 16 = n^2 - 6n - 16

Added 12/4/2014 10:13:35 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [12/4/2014 10:42:10 PM]

34,446,933

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 590 [Total 6463] Ratings 10 Comments 490 Invitations 0 Offline

There are no comments.